Gestión de los procesos productivos en la industria cafetera - Guerrero Suárez, Katherine Anabel (2023)
The documentation of the productive processes in the company of Café S.A. It has a fundamental role, due to its importance in the analysis of each professional belonging to the soluble coffee processes, for this reason this work has as its general objective the documentation of the coffee drying production processes and this contributes to the determination of the raw material yield. One of the objectives of this work will allow to understand and understand the components of each process and likewise creates a generic model that will be used for decision making. Chapter 3 consisted of the elaboration of the methodological framework, whose research approach was mixed, due to the use of quantitative and qualitative data, while the type of research was explanatory, documentary and descriptive. In this same chapter, through the use of the interview, the result was the lack of a generic model that allows analyzing the costs by processes, while in the documentary analysis, a drop in profit margins due to COVID-19 can be seen. For this reason, it is concluded that the entities belonging to this sector must apply the process model for decision making.